Chin augmentation with conchal cartilage - Viterbo, Fausto [UNESP] (Wolters Kluwer, 2003)
Profile enhancement most frequently involves mentoplasty. For this purpose, the author performs conchal grafts to the chin. A total of 28 women aged 15 to 76 years (mean age, 38.11 ± 15.11 years) requested mentoplasty by itself or combined with rhinoplasty, rhytidoplasty, or submental lipoplasty. The conchal cartilage was harvested subperichondrally through a posterior 3-cm incision. The specimen measured 3 x 1 cm, which was sufficient to project the chin 2 to 3 mm. For 4 to 5 mm of projection, both cartilages were used. The graft was positioned under the periosteum and held with two 5-0 nylon sutures. In these cases, the conchal cartilage graft was a suitable option for chin augmentations up to 5 mm.
Keywords: Adolescent; Adult; Aged; Cartilage graft; Chin; Clinical article; Esthetic surgery; Eyelid reconstruction; Female; Human; Liposuction; Mandible reconstruction; Nose reconstruction; Priority journal; Surgical technique; Treatment outcome; Blepharoplasty; Cartilage; Combined Modality Therapy; Lipectomy; Middle Aged; Rhinoplasty; Rhytidoplasty; Surgery, Plastic